Haemato-biochemical response to lumbar epidural anaesthesia using bupivacaine alone and in combination with certain analgesics in buffalo calves - Md. Osamah Kalim; Shailendra Kumar Tiwari; Raju Sharda; Poonam Vishwakarma (The Iranian Journal of Veterinary Science and Technology, 2011)
The present study was undertaken to evaluate the efficacy of bupivacaine alone and in combination with fentanyl and edetomidine for lumbar epidural analgesia in fifteen buffalo calves. Haemato-biochemical parameters viz- Hb PCV, TLC, DLC, serum glucose, Serum Total protein, Serum urea nitrogen, Serum Creatinine, AST and ALT were measured after lumbar epidural administration of bupivacaine alone (group A), bupivacaine with fentanyl (group B) and bupivacaine with medetomidine (group C) animals (@ 0.15mg/kg body wt., 0.15mg/kg body wt + 2μgm/kg body wt, 0.15mg/kg body wt.+ 15μgm/kg body wt) respectively. Haematological studies revealed a not really significant decrease in Hb, PCV and TLC in group A and B, a significant (p